EXTENT ENTREPRENEURIAL ORIENTATION IMPROVES THE PRODUCTIVITY OF SMES IN DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study investigated the extent entrepreneurial orientation improves the productivity of SMEs in Delta State. Two research questions guided the study while four null hypotheses were formulated. The study adopted the descriptive survey research design. The population for this study consisted 1,310 promoters of small and medium scale enterprises registered with the Delta State Ministry of Trade, Commerce and Industry. A sample of 393 entrepreneurs or managers of small and medium scale enterprises in Delta State was used for the study using proportionate stratified sampling technique. The questionnaire titled “Entrepreneurial Orientation and Productivity of Small and Medium Scale Enterprises Questionnaire” (EOPSMSEQ) was developed by the researcher. Face validity of the instrument was established using the opinions of experts. Cronbach alpha was used to determine the internal consistency of the instrument and it yielded an overall co-efficient of 0.79. Arithmetic mean and standard deviation was used to answer the research questions while Analysis of Variance (ANOVA) was used to test the null hypotheses at 0.05 alpha level. The findings revealed that entrepreneurs of SMEs in Delta State are of the opinion that entrepreneurs’ merger internship and marketing strategies determine the productivity of SMEs to a high extent. The findings also revealed that entrepreneurs of SMEs in Delta State do not differ significantly in their mean ratings on the extent entrepreneurs’ merger internship and marketing strategies in determining the productivity of SMEs based on years of experience.
Keywords: Entrepreneurship Orientation; Productivity; Small and Medium Scale Enterprises